175 Oncology in a benign gynecology department. (18th September 2019) - Glennon, K; Cleary, S; Von Banau, G
Abstract : Objectives: To assess the extent the contribution of a gynaecological service in a non-designated hospital makes to the investigation of cancer. Assessment of the imaging and histopathology work up of cancer patients prior to referral or transfer to a dedicated gynae-oncology centre. Methods: This was a retrospective cohort study concentrating on all cancer diagnoses in a benign gynaecological unit from 2012–2018. Patients were identified from the department archive of referrals to the gynae-oncology department, the histopathology SNOWMED system and radiological database. The patient data was analysed using Microsoft excel Results: Since 2012 – December 2018, 239 cases of endometrial or cervical cancer were diagnosed (endometrial=125 cervical=113). The mean age of cervical cancer patients was 44 years (29 – 84) and endometrial cancer patients was 63 years (41 – 88). Ninety percent of patients had imaging prior to transfer to the gynae-oncology department (MRI=105, CT-TAP=112). Suspicious complex ovarian masses diagnosed on CT or MRI also required MDT discussion (2018 n=33). The patients were referred to the gynaeoncology MDT in the tertiary system following complete work up. Conclusions: The contribution of a benign gynaecological centre to cancer care in Ireland is significant. Significant resources are availed of prior to referral to the tertiary centre. Currently there is no dedicated oncological nurse for our department. This research highlights that a dedicated integrated referral system and access to an oncology liaison would ensure swift and timely access to gynae-oncology services for the many patients that present to benign centres.